2003
DOI: 10.1002/hipo.10128
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of hippocampal and rhinal cortex volumes in patients with mesial temporal sclerosis

Abstract: Considerable progress has been made toward understanding the function of the primate rhinal cortex, comprising the entorhinal (ErC) and perirhinal (PrC) cortices. However, translating animal models to human memory has been limited by the technological problems associated with characterizing neural structures in vivo. Functional correlates of hippocampal and rhinal cortex volume changes were examined in a sample of 61 temporal lobe epilepsy patients with mesial temporal sclerosis (MTS; 33 left, 28 right). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
See 1 more Smart Citation
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
“…The association between right hippocampal volumes and nonverbal learning and memory is tenuous, but has been reported in a few studies (7,10,11). In addition, there are data to support the role of other medial temporal lobe structures in verbal and visual memory, including the amygdala (8,12), mammillary bodies (8), and perirhinal cortex (9,13). In fact, there is some evidence that right amygdala volume is a stronger predictor of visual memory than right hippocampal volume (8,12).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 99%
“…We were also unable to demonstrate any consistent damage to the perirhinal cortex in rats exposed to various durations of pilocarpine-induced status epilepticus (Benini et al, 2011; Gualtieri et al, 2012), a finding further confirmed by staining necrotic cells with Fluoro-Jade (Figure 5) (Biagini et al, 2005, 2008). These experimental findings are at odds with clinical data showing that the perirhinal cortex presents with consistent asymmetries when the region ipsilateral to the sclerotic hippocampus is compared with the contralateral (Bernasconi et al, 2000, 2003; Salmenperä et al, 2000; Jutila et al, 2001; O'Brien et al, 2003; Alessio et al, 2006; Guedj et al, 2010). These discrepancies may have several explanations.…”
Section: Interneurons Are Selectively Damaged In the Pilocarpine Modementioning
confidence: 92%
“…Neuropsychological research in chronic temporal lobe epilepsy (TLE) has focused on hippocampal integrity and its corresponding impact on episodic memory Lui et al, 2005;Martin et al, 1999;O'Brien et al, 2003). However, recent evidence has demonstrated that TLE is characterized by abnormalities in brain regions that extend beyond the affected hippocampus (Hermann et al, 2003;Marsh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus has been extensively examined in unilateral TLE, and there is general agreement that the ipsilateral hippocampus (epileptogenic) is more atrophied than the contralateral hippocampus, that both early neurodevelopmental and course variables affect the ipsilateral hippocampus but not contralateral hippocampus (Bernasconi et al, 2005;Jack, 1994;Theodore et al, 1999;Van Paesschen et al, 1997), and that memory functioning is associated with hippocampal integrity Lui et al, 2005;Martin et al, 1999;O'Brien et al, 2003).…”
Section: Introductionmentioning
confidence: 99%